(3CHQR GdeYGfj ef MQR GdCeGfjs - (3CHh TGeI YHO GdQMef Hf ESeGYjd GdOeTbjs; (3GdTGWHj GdebQF GdVQjQ , CHh eMeO,J (B590 (3g` s ((3EHQGgje Ydi s)
(3ChdgG (B:s
(3CeG HYO aEf Chdi eG Cafi ajg Gdecda YeQg hYda Hg NGWQg hGYed ajg acQg JMUjd GdYdhe GdfGaYI GdTQYjI s
(3BNQgG (B:s
(3ChRfLHjd gh YfOi CWjH hGdRQfH hGdbQfad Ohf GdeSc hGdefOd ai GdWjH aMSf JTHjg GdUhI Ydi GdUMGHg HPdc Je EHQGR GdeYGfi GdeNJUQ HMeO Gddg s
(3GdfSNI HgG MhGTs
(3MQR GdCeGfi hhLg GdbQBf GdeYQha HGdbUjOI GdTGWHjIs
(3fSNI Chdi s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs